Mechanism of NO reduction to NH3 on Fe single- and double-atom catalyst active sites supported at graphitic edges: A first-principles study - Reva Budiantono; Kenta Hongo; Ni Luh Wulan Septiani; Muhammad Iqbal; Tetsuya Kida; Adhitya Gandaryus Saputro; Muhammad Haris Mahyuddin (Fuel, 2026)

A sustainable mechanical engineering framework for biomaterials in healthcare system development - Helal Uddin; Laraib Zanib; Izzah Atif; Basmalaa Ahmed Thabet; Zaryab Basharat; Muhammad Haris Malik; Faheem Ahmad (Next Research, 2026)

MOF-derived FeCuMn mixed phase photocatalysts for advanced oxidation of microplastics via synergistic charge transfer and multipath reactive oxygen species generation - Muhammad Haris Khan; Xiaoshu Wang; Wenqin Wu; Zareen Zuhra; Shafqat Ali; Zhang Zhaowei (Journal of Water Process Engineering, 2026)

Performance analysis of a helium-nitrogen binary gas mixture centrifugal compressor for terrestrial gas-cooled reactor power plants of closed Brayton cycles - Arif Aziz; Qun Zheng; Adil Malik; Muhammad Haris; Ghulam Ishaque; Shadman Ahmad Khattak (Annals of Nuclear Energy, 2026)

Energy poverty and wealth under economic and energy policy uncertainty - Sonia Hassan; Muhammad Haris (Energy Policy, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular characterization and in silico analysis of the malate dehydrogenase (MDH) gene family in wheat (Triticum aestivum L.) with expression profiling under heavy metal stresses - Mingfang Yang; Amna Abdul Rahim; Haris Khurshid; Laraib Malik; Mohamed A. El-Sheikh; Hafiz Mamoon Rehman; Yingping Tian; Muhammad Arif (Journal of Hazardous Materials, 2026)

Scalable room-temperature synthesis of a MOF-based magnetic adsorbent for rapid simultaneous removal of PFAS and micro-nanoplastics - Muhammad Haris; Fozia Bibi; Suraj Loomba; Karishma Jain; Nasir Mahmood; Nicky Eshtiaghi (Chemical Engineering Journal, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

Z-scheme charge transfer–driven peroxymonosulfate activation over MIL-53-NH₂(Fe)/Bi₂WO₆ for mechanistic degradation of polystyrene microplastics - Fei Meng; Muhammad Haris Khan; Shafqat Ali; Zareen Zuhra; Dugang Chen; Zhaowei Zhang (Journal of Environmental Chemical Engineering, 2026)

Correction to: A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)

A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)
Oral cavity cancers are a debilitating form of head and neck cancer with high rates of mortality. Radiotherapy is one of the main forms of treatment but relies on minimizing doses that are delivered to organs at risk and considering any motion in the mouth. One solution is to use a block within the mouth which acts to reduce motion and decreases tissue heterogeneity. In this work, we developed a process for designing a customized tissue-equivalent 3D-printed tongue bite and evaluated its impact on the radiation treatment. Six patients with stage III or IV oral cancer were involved. Computed tomography (CT) images for each patient were acquired with currently used Styrofoam tongue bites within the mouth. The designs of 3D tongue bites were prepared using those CT images and then printed on an SLA printer using F80 resin which is a tissue-equivalent and biocompatible material. Secondary CT images were then acquired for each patient with the 3D tongue bites to have a dosimetric comparison. Volumetric-modulated arc therapy (VMAT) planning was carried out for individual patients on both CT images. Plan parameters, fractionation scheme and optimization priorities were all kept the same. The radiotherapy plans utilizing 3D tongue bites showed better PTV coverage and reduced D max ( p = 0.028). Doses to organs at risk (OARs) including brainstem, parotid glands and hard palate were also reduced ( p < 0.028) except for the spinal cord ( p > 0.05). The dose conformity and homogeneity were also improved ( p = 0.028 and p = 0.044 respectively). All patients reported that the 3D tongue bites were soft, conformal to the oral cavity, comfortable and did not cause any gag reflex. We conclude that the 3D tongue bite is a useful utility that improves the treatment of patients with oral cancer.

Catboost regressor for monsoon rainfall forecasting in Malaysia using atmospheric Beryllium-7 concentration - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Mohd Zaid Hassan Abdul Rahman; Nur Fatini Abdul Ghani; Muhammad Rawi Mohamed Zain (Modeling Earth Systems and Environment, 2026)

Disaster management technology and approaches: a focus on heterogeneous systems - Muhammad Haris; Sajjad Keshtkar; Adeel Anjum; Madiha Haider Syed; Hirohisa Kojima; Rafiq Ahmad (Environment Systems and Decisions, 2026)

Exploring the Role of Mitochondrial Sirtuin 3 Gene in Gastric Cancer Risk Based on SNP Analysis and LORD-Q Assay - Ishrat Mahjabeen; Muhammad Zahid Hussain; Maria Fazal-Ul Haq; Azhar Mehmood; Muhammad Shahbaz Haris; Shereen Ali Khan; Anum Chaudhry; Farzana Hakim; Ayesha Zulfiqar Abbasi; Mahmood Akhtar Kayani (Biochemical Genetics, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Advancing Spatiotemporal Orthophoto Registration in UAV-based Crop Breeding Experiments Leveraging Field Geometric Features - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Haris Khurshid; M. R. Naseem; Karsten Berns; Muhammad Moazam Fraz (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2026)

Black carbon and its relationship with PM2.5 and NO2 in a high-traffic urban environment of Kuala Lumpur - Murnira Othman; Mohd Talib Latif; Haris Hafizal Abd. Hamid; Ethel Garcia; Muhammad Ikram A. Wahab; Santhyami Santhyami; Li Li (Urban Climate, 2026)

Holistic review on Paenibacillus: The multifunctional genus in heavy metal detoxification, pesticide degradation, and abiotic stress mitigation for Sustainable Agriculture - Izhar Khan; Nadeem Ullah; Haris Maqbool; Adnan Hashmi; Basit Khan; Afnan Khalid; Iffat Naz; Najeeba Parre Paker; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Plant and Soil, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

Characterization and diversity of indigenous and exotic groundnut (Arachis hypogaea L.) accessions adapted to agro-ecological conditions in Pakistan - Muhammad Jahanzaib; Haris Khurshid; Ihsanullah Khan; Awais Rasheed (Genetic Resources and Crop Evolution, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Assessment of microbial remediation potential of indigenous bacterial and fungal communities for toxic heavy metal sequestration - Afnan Khalid; Haris Maqbool; Izhar Khan; Basit Khan; Iffat Naz; Shanza Abdul Qayyum; Javed Ali; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2025)

Cell wall polysaccharides response to cadmium stress and transcriptome analysis in tomato (Solanum lycopersicum) - Min Wang; Muhammad Haris; Chao Zhang; Ting Wei; Lei Zhang; Minwang Laipan; Junkang Guo (Plant Science, 2025)

Coordination engineering of MOF-derived bimetallic catalysts for advanced oxidation of organic pollutants - Zareen Zuhra; Muhammad Haris Khan; Saba Sharafat; Shafqat Ali; Zhang Zhaowei (Journal of Environmental Chemical Engineering, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Systematic study on the relationship between Beryllium-7 concentration with dynamics of northeast monsoon activity - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Muhammad Rawi Mohamed Zin; Mohd Zaid Hassan Abdul Rahman; Haizum Ruzanna Sahar; Azlai Ta'at (Journal of Environmental Radioactivity, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

Dose-dependent efficacy and safety of Filgotinib in moderate to severe Crohn’s disease: a grade-assessed systematic review and meta-analysis of randomized controlled trials - Mohamed S. Elgendy; Ahmed Raza; Mohamed Rifai; Wajeeh Ur Rehman; Ahmed Emara; Muhammad Haris Khan; Ayiz Jan; Muhammad Younas; Anum Nawaz; Ubaid Khan (European Journal of Clinical Pharmacology, 2025)

Dynamic modeling and optimal control schemes for an offshore-wind powered direct air capture system with energy storage options - Muhammad Faisal Shehzad; Haris Ishaq; Curran Crawfrod (Science of The Total Environment, 2025)

Zero-carbon solution: Microalgae as a low-cost feedstock for fuel production and carbon sequestration - Moeen Ali Rashad; Farrukh Jamil; Murid Hussain; Abrar Inayat; Parveen Akhter; Muhammad Haris Hamayun; Ali Ahsan; Young-Kwon Park (Critical Reviews in Environmental Science and Technology, 2025)

Challenges and Strategies in Managing Naegleria fowleri-Associated Primary Amoebic Meningoencephalitis in Pakistan: A Case Report - Maham Zaman; Tooba Fida; Hafiz Muhammad Haris; Zarmeen Naveed; Shaheer Haider; Tauqeer Khan (Acta Parasitologica, 2025)

Dynamic ARDL simulations of Pakistan’s energy intensity: the role of non-fossil energy, innovation, and financial development - Muhammad Haris Hanif (Environment, Development and Sustainability, 2025)

Scalable interlinked hierarchical porous biochar-nanosheets for efficient removal of thallium from aquatic environment - Haitao Ren; Zainab Amjad; Atif Saleem; Muhammad Usman; Kukybayeva Dina; Muhammad Haris; Junkang Guo (Journal of Hazardous Materials, 2025)

Impact of fiscal and green fiscal indicators on climate and environmental variability: the moderating role of technological innovation - Muhammad Haris; Sonia Hassan; Aviral Kumar Tiwari; HongXing Yao (Environment, Development and Sustainability, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

Assessment of Susceptibility of Potato (Solanum tuberosum L.) Cultivars to Root Lesion Nematode, Pratylenchus penetrans, and Disease Impact on Plant Growth and Tuber Weight - Nehan Ain; Ishrat Naz; Maria; Syed Sartaj Alam; Muhammad Haris (Potato Research, 2025)

CO2 capture using mixed amines: experimental DFT investigation with focus on improvements in cyclic efficiency and NO interference - Muhammad Haris; Arif Aziz; Muhammad Sohail; Waseem Sardar (Environmental Science and Pollution Research, 2025)

Is There Any Role of Zinc and Copper in Severity and Progression of Osteoarthritis? A Review - Umaima Cheema; Meeram Noor; Hurain Naeem; Mahnoor Arfan; Abdul-Rehman Azam; Shamikha Cheema; Hafiz Muhammad Haris; Muhammad Raza (Biological Trace Element Research, 2025)

Impact of sulfur-ash reduction treatment on combustion performance, SOx emissions, and flue gas temperatures of lignite coals: experimental and computational study - Mansoor Ahmed Lakhmir; Faheem Akhter; Jawad Ahmed; Sidra Mushtaq; Haris Jawad Arain; Muhammad Junaid Ahsan (Environmental Science and Pollution Research, 2025)

Transfer dynamics of antimicrobial resistance among gram-negative bacteria - Bangjuan Wang; Muhammad Haris Raza Farhan; Linlin Yuan; Yuxin Sui; Jinhua Chu; Xiaohan Yang; Yuxin Li; Lingli Huang; Guyue Cheng (Science of The Total Environment, 2024)

Fabrication of Iron Oxide–Based Chitosan/CNF Bio-Green Composite for Pb(II) Removal from Synthetic Wastewater: Isotherm and Regeneration Studies - Faheem Akhter; Jawad Ahmed; Waseem khan; Abdul Rehman Jatoi; Mansoor Ahmed Lakhmir; Muhammad Junaid Ahsan; Haris Jawad Arain; Shareen Bhurgri; Niaz Muhammad Laghari; Irfan Ali Sanjrani (Water Conservation Science and Engineering, 2024)

Green Pesticide High Activity Based on TiO2 Nanosuspension Incorporated Silver Microspheres Against Phytophthora palmivora - Zul Arham; Annisa Zalfa Al Ikhwan; Muhammad Edihar; Abdul Haris Watoni; Irwan Irwan; Muhammad Nurdin; Maulidiyah Maulidiyah (Indian Journal of Microbiology, 2024)

Physiological characteristics of ornamental caladiums (Caladium x hortulanum Birdsey, Araceae Juss.) through leaf colour diversity - Rahmat Budiarto; Syariful Mubarok; Jajang Sauman Hamdani; Muhammad Achirul Nanda; Moh Haris Imron S Jaya; Siti Auliya Rahma; Muhamad Abdul Rofiq; Supatida Abdullakasim (South African Journal of Botany, 2024)

Metal-organic frameworks for sustainable precious metal recovery: A review of recent advances - Zareen Zuhra; Muhammad Haris Khan; Shafqat Ali; Muhammad Ahmad; Zhang Zhaowei (Chemical Engineering Journal, 2024)

Functionality of wheat straw-derived biochar enhanced its efficiency for actively capping Cd and Pb in contaminated water and soil matrices: Insights through batch adsorption and flow-through experiments - Yasir Hamid; Yonglong Chen; Qiang Lin; Muhammad Haris; Muhammad Usman; Muhammad Saqib Rashid; Ioannis Anastopoulos; Bilal Hussain; Hayssam M. Ali; Fakhir Hannan; Xianyuan Yin; Xiaoe Yang (Chemosphere, 2024)

Analysing landscape multi-functionality by integrated modelling - Borjana Bogatinoska; Angelique Lansu; Jean Hugé; Muhammad Haris Ali; Stefan C. Dekker; Jetse Stoorvogel (Environmental Modelling & Software, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

Anti-inflammatory and analgesic properties of Polyphyllin VI revealed by network pharmacology and RNA sequencing - Zhenglang Zhang; Tingting Wang; Zhenhui Luo; Muhammad Haris Zaib; Mengqin Yi; Hekun Zeng; Peiyang Li; Dan Tang; Alexei Verkhratsky; Hong Nie (Purinergic Signalling, 2024)

Characterization of two novel fusariviruses co-infecting a single isolate of phytopathogenic fungus Botrytis cinerea - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Nasar Virk; Muhammad Faraz Bhatti (Virus Genes, 2024)

Biochar-based functional materials for the abatement of emerging pollutants from aquatic matrices - Lei Wang; Jian Zhang; Dongle Cheng; Wenshan Guo; Xiaoqiang Cao; Jianliang Xue; Muhammad Haris; Yuanyao Ye; Huu Hao Ngo (Environmental Research, 2024)

Maize productivity and nutrient status in response to crop residue mineralization with beneficial microbes under various tillage practices - Haris Khan; Ahmad Khan; Sajid Khan; Anjum Anjum; Habib Akbar; Dost Muhammad (Soil and Tillage Research, 2024)

Insight into the wheat residues-derived adsorbents for the remediation of organic and inorganic aquatic contaminants: A review - Muthanna J. Ahmed; Ioannis Anastopoulos; Dimitrios Kalderis; Muhammad Haris; Muhammad Usman (Environmental Research, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

The concentration of particulate matters in mechanically ventilated school classroom during haze episode in Kuala Lumpur City Centre - Azwani Alias; Mohd Shahrul Mohd Nadzir; Mohd Talib Latif; Md Firoz Khan; Haris Hafizal Abd Hamid; Mazrura Sahani; Muhammad Ikram A. Wahab; Murnira Othman; Faizal Mohamed; Noorlin Mohamad; Norhaniza Amil; Otuyo Muhsin Kolapo (Air Quality, Atmosphere & Health, 2024)

Non-lamellar lyotropic liquid crystalline nanoparticles as nanocarriers for enhanced drug encapsulation of atorvastatin calcium and proanthocyanidins - Mardhiah Maslizan; Muhammad Salahuddin Haris; Mokrish Ajat; Siti Nurul Ain Md Jamil; Shah Christirani Azhar; N. Idayu Zahid; Intan Diana Mat Azmi (Chemistry and Physics of Lipids, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Electricity shortfalls and financial leverage of listed firms in Pakistan - Muhammad Akhtar; Muhammad Haris; Hafiz Muhammad Naveed; Yasir Rasool; Mamdouh Abdulaziz Saleh Al-Faryan (Utilities Policy, 2024)

Study of ceramsite-supported iron and manganese oxides for enhancing soil immobilization and reducing rice plants uptake of cadmium - Xianwei Yu; Chao Zhang; Muhammad Haris; Cui Chen; Huan Wang; Jin Guo; Haojiang Meng; Xiaolong Wu; Xiaoyang Liu; Weiwei Hu; Junkang Guo (Journal of Environmental Chemical Engineering, 2024)

Agro-morphological characterization and genetic variability assessment of soybean [Glycine max (L.) Merr.] germplasm for yield and quality traits - Atta Ullah; Zahid Akram; Ghulam Rasool; Muhammad Waris; Haris Khurshid (Euphytica, 2024)

A review on endophytic fungi: a potent reservoir of bioactive metabolites with special emphasis on blight disease management - Murad Muhammad; Abdul Basit; Kashif Ali; Haris Ahmad; Wen-jun Li; Ayesha Khan; Heba I. Mohamed (Archives of Microbiology, 2024)

Efficient sorption of As(III) from water by magnetite decorated porous carbon extracted from a biowaste material - Fozia Bibi; Rafaqat Hussain; Ahson Jabbar Shaikh; Muhammad Waseem; Naseem Iqbal; Suraj Loomba; Muhammad Haris; Nasir Mahmood (Environmental Science and Pollution Research, 2024)

Potential of milk fat globule membrane's phospholipids and anhydrous milk fat based nanostructured lipid carriers for enhanced bioaccessibility of vitamin D3 - Bina Zarif; Muhammad Haris; Ramla Shahid; Tauqir A. Sherazi; Abdur Rahman; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Influence of Oxyranylmethanol as a Catalytic Cross-linking Agent over Physiochemical Properties and Pb (II) Adsorption Performance of Resorcinol Formaldehyde Aerogels: a Comparative Study - Faheem Akhter; Abdul Rauf Jamali; Jawad Ahmed; Haris Jawad Arain; Muhammad Junaid Ahsan; Muhammad Naeem Akhtar (Water, Air, & Soil Pollution, 2023)

Inquiring the impact of rural–urban migration, construction sector, and agriculture irrigated land on environmental degradation: insights from urbanized Asian countries - Feng Guoru; Muhammad Haris Hanif; Usman Saleem Yousaf (Environmental Science and Pollution Research, 2023)

Sustainable assessment of an integrated energy system coupled with solar thermochemical cycle - Muhammad Ishaq; Haris Ishaq (Journal of Cleaner Production, 2023)

Metal-Doped Carbon Dots (MCDs) as Efficient Nano-adsorbents for Detection, Monitoring, and Degradation of Wastewater Pollutants: Recent Progress, Challenges, and Future Prospects - Faheem Akhter; Jawad Ahmed; Munawar Ali Pinjaro; Fahad Ahmed Shaikh; Haris Jawad Arain; Muhammad Junaid Ahsan (Water, Air, & Soil Pollution, 2023)

Investigating the effects of matrix acidizing and acid fracturing on the production optimization of a carbonate reservoir: a case study - Umair Qureshi; Haris Ahmed Qureshi; Amanat Ali Bhatti; Muhammad Salman Saeed; Muhammad Sameer Khalid (Arabian Journal of Geosciences, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Cellulose-based adsorbent materials for water remediation: Harnessing their potential in heavy metals and dyes removal - Awais Ali Aslam; Sadaf Ul Hassan; Muhammad Haris Saeed; Osama Kokab; Zulfiqar Ali; Muhammad Shahid Nazir; Waleed Siddiqi; Aamir Ali Aslam (Journal of Cleaner Production, 2023)

Novel thiol-grafted composite of chitosan and rice straw biochar (TH@CT-BC): A two-step fabrication for highly selective adsorption of cadmium from contaminated water - Yasir Hamid; Lei Liu; Muhammad Haris; Muhammad Usman; Qiang Lin; Yonglong Chen; Muhammad Saqib Rashid; Zaid Ulhassan; M. Iftikhar Hussain; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2023)

How flare-up of small and medium enterprises intensifies carbon emissions in Asian and European regions: a panel analysis - Han Fei; Muhammad Haris Hanif; Imran Hanif (Environmental Science and Pollution Research, 2023)

Large-scale wind power grid integration challenges and their solution: a detailed review - Muhammad Shahid Mastoi; Shengxian Zhuang; Malik Haris; Mannan Hassan; Asif Ali (Environmental Science and Pollution Research, 2023)

Oxide vacancy passivation through interface engineering of Tetraphenylethylene-Based Small-Molecule with sulfonate functional group for efficient organic photodetector - Woongsik Jang; Zia Ur Rehman; Muhammad Haris; Jae Sang Cho; Jihyun Lim; Min Soo Kim; Jong-Cheol Lee; Hang Ken Lee; Dong Hwan Wang (Chemical Engineering Journal, 2023)

Drinking Water Quality Assessment of Government, Non-Government and Self-Based Schemes in the Disaster Affected Areas of Khyber Pakhtunkhwa, Pakistan - Javed Nawab; Abdur Rahman; Sardar Khan; Junaid Ghani; Zahid Ullah; Haris Khan; Muhammad Waqas (Exposure and Health, 2023)

The presence of mycoviral infection attenuates the growth and pathogenicity of the phytopathogenic fungus Botrytis cinerea collected from strawberry fields in Pakistan - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Danish Ilyas Baig; Tehsin Fatma; Nasar Virk; Muhammad Faraz Bhatti (European Journal of Plant Pathology, 2023)

Mycovirus-induced hypovirulence in notorious fungi Sclerotinia: a comprehensive review - Haris Ahmed Khan; Mamuna Mukhtar; Muhammad Faraz Bhatti (Brazilian Journal of Microbiology, 2023)

Experimental behaviour of unreinforced and confined rat-trap bond masonry - Muhammad Haris; Mohammad Ashraf; Muhammad Fahim; Samiullah (European Journal of Environmental and Civil Engineering, 2023)

Opening a new horizon in green HRM practices with big data analytics and its analogy to circular economy performance: an empirical evidence - Ka Yin Chau; Tian Huang; Massoud Moslehpour; Waqas Khan; Qasim Ali Nisar; Muhammad Haris (Environment, Development and Sustainability, 2023)

Sedimentology and reservoir characteristics of Jurassic Samanasuk Formation of Salt Range and Hazara areas, Upper Indus Basin, Pakistan - Syed Umair Ali; Syed Kamran Ali; Khawaja Umair Majeed; Muhammad Haris; Muhammad Zaheer; Tariq Mehmood (Arabian Journal of Geosciences, 2023)

Synthesis of a micro-nano FeOx/MnOx modified large volume non-enamel ceramsites for selective and efficient adsorption of cadmium - Junkang Guo; Xianwei Yu; Muhammad Haris; Tian Liu; Jiayuan Wang; Junjun Zhao; Yifan Li; Chao Zhang (Journal of Environmental Chemical Engineering, 2023)

Mine waste water self-purification (arsenic) in neutral hydrogeochemical ecosystem: A case study from V-Ti-Fe mine tailings - Lei Xu; Liang Tang; Xiaolin Zhang; Zhengmeng Hou; Muhammad Haris; Jiashun Luo; Yuanliang Yang (Geochemistry, 2023)

Finite-time active fault-tolerant attitude control for flexible spacecraft with vibration suppression and anti-unwinding - Muhammad Noman Hasan; Muhammad Haris; Shiyin Qin (Advances in Space Research, 2023)

Modelling of geomorphological features of fluvial systems in Eromanga Basin and North Sea using 3D seismic attributes - Haris Ahmed Khan; Saifullah Abdul Qadir; Muhammad Jahangir Khan; Faraz Hasan Siddiqui; Mirza Saad Ahsan (Journal of Earth System Science, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Self-assembly of C@FeO nanopillars on 2D-MOF for simultaneous removal of microplastic and dissolved contaminants from water - Muhammad Haris; Muhammad Waqas Khan; Ali Zavabeti; Nasir Mahmood; Nicky Eshtiaghi (Chemical Engineering Journal, 2023)

Characterization and implication of microplastics on riverine population of the River Ravi, Lahore, Pakistan - Muhammad Haris Raza; Farhat Jabeen; Salma Ikram; Saba Zafar (Environmental Science and Pollution Research, 2023)

Identification of novel totiviruses from the ascomycetous fungus Geotrichum candidum - Haris Ahmed Khan; Hideki Kondo; Sabitree Shahi; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2022)

Successful matrix stimulation and wax cleaning of a high water cut oil well of east Potwar region: A case study - Haris Ahmed Qureshi; Ali Ahmed Pathan; Temoor Muther; Ubedullah Ansari; Muhammad Hanif Chachar (Arabian Journal of Geosciences, 2022)

Promising role of polymeric nanoparticles in the treatment of rheumatoid arthritis - Rida Siddique; Malik Hassan Mehmood; Muhammad Haris; Ammara Saleem; Zunera Chaudhry (Inflammopharmacology, 2022)

Lifecycle cost analysis of an insulated duct with an air gap - Dileep Kumar; Muhammad Haris Khan; Muhammad Ali Abro (Environmental Science and Pollution Research, 2022)

A novel victorivirus from the phytopathogenic fungus Neofusicoccum parvum - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2022)

Inducible knockdown of Mycobacterium smegmatis MSMEG_2975 (glyoxalase II) affected bacterial growth, antibiotic susceptibility, biofilm, and transcriptome - Muhammad Haris; Changming Chen; Jing Wu; Muhammad Noman Ramzan; Ayaz Taj; Shanshan Sha; Hayan Ullah; Yufang Ma (Archives of Microbiology, 2022)

Recent updates on immunological, pharmacological, and alternative approaches to combat COVID-19 - Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Haris; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

A second capsidless hadakavirus strain with 10 positive-sense single-stranded RNA genomic segments from Fusarium nygamai - Haris Ahmed Khan; Yukiyo Sato; Hideki Kondo; Atif Jamal; Muhammad Faraz Bhatti; Nobuhiro Suzuki (Archives of Virology, 2021)

Feasibility study and modeling of solar generated steam for heavy oil recovery - Haris Ahmed Qureshi; Temoor Muther; Ubedullah Ansari; Ali Ahmed Pathan; Muhammad Hanif Chachar (Arabian Journal of Geosciences, 2021)

Exploring the relationships among CO2 emissions, urbanization, economic growth, economic structure, energy consumption, and trade along the BRI based on income classification - Jiying Wu; Olivier Joseph Abban; Alex Dankyi Boadi; Muhammad Haris; Patrick Ocran; Antoinette Asabea Addo (Energy, Ecology and Environment, 2021)

Nexus on climate change: agriculture and possible solution to cope future climate change stresses - Aqeel Shahzad; Sana Ullah; Afzal Ahmed Dar; Muhammad Fahad Sardar; Tariq Mehmood; Muhammad Aammar Tufail; Awais Shakoor; Muhammad Haris (Environmental Science and Pollution Research, 2021)

Histomorphology of Seminal Vesicles Subsequent to Exogenous Neurokinin B Administration in New Zealand White Rabbits - Zain Ullah; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

An overview of polymeric nano-biocomposites as targeted and controlled-release devices - Muhammad Rahim; Mas Rosemal Hakim Mas Haris; Najm Us Saqib (Biophysical Reviews, 2020)

Exogenous Neurokinin B Administration May Have a Strong Effect on Negative Feedback Loop of Hypothalamic Pituitary Thyroid Axis - Maria Wishal Asmat; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Risk Assessment of Work Accident in Container Terminals Using the Fault Tree Analysis Method - Muhammad Arif Budiyanto; Haris Fernanda (Journal of Marine Science and Engineering, 2020)
The use of containers in the world is increasing every year in line with international trade flows. In very complex container terminal operations, the risk of work accidents is inevitable and can happen at any time. Therefore, this paper aimed to identify accidents and potential risks occurring in the container terminals. For the case study, the analysis was used the data of accidents during five years in one of the major container terminals in Indonesia. Risk assessment is carried out using the risk matrix method to get the level of risk. The risk that has the highest level is analyzed by using the Fault Tree Analysis method. From the results of the risk assessment shows the container fell to the berth when loading and unloading have the highest risk value. While the results of the Fault Tree Analysis show that traffic accidents are the biggest potential risk, which is 41.8% compared to other accidents. Moreover, human factors especially due to the negligence in operating vehicles or equipment as well as the damage of equipment were the highest common causes of accidents in the container terminal. Based on these results the contribution offered is the risk control options for terminal operators to reduce the possibility of safety failure in the container terminal.

Evaluating the environmental effects of economic openness: evidence from SAARC countries - Hua-ping Sun; Gulzara Tariq; Muhammad Haris; Muhammad Mohsin (Environmental Science and Pollution Research, 2019)

Plio-Pleistocene stratigraphic sequences and depositional model using 3D seismic interpretation constrained by well logs in Central Graben, North Sea - Haris Ahmed Khan; Taher Zouaghi; Shaista Iftekhar; Muhammad Jahangir Khan; Muhammad Irfan (Journal of Earth System Science, 2019)

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Characterization of rainwater chemical composition after a Southeast Asia haze event: insight of transboundary pollutant transport during the northeast monsoon - Mohd Shahrul Mohd Nadzir; Chin Yik Lin; Md Firoz Khan; Mohd Talib Latif; Doreena Dominick; Haris Hafizal Abdul Hamid; Noorlin Mohamad; Khairul Nizam Abdul Maulud; Muhammad Ikram Abdul Wahab; Nurul Farahana Kamaludin; Mohamad Azwani Shah Mat Lazim (Environmental Science and Pollution Research, 2017)